MODERASI PARTISIPASI MASYARAKAT DAN TRANSPARANSI KEBIJAKAN PUBLIK DALAM PENGARUH PENGETAHUAN ANGGOTA DPRD TENTANG ANGGARAN TERHADAP PENGAWASAN KEUANGAN DAERAH - Candra Winata; Dewi Amalia (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2013)
A change in the characteristics of the traditional budget to budget performance requires legislators to understand the changes. This causes the function of members of parlement to be very important in the process of preparation, approval, and oversight the budget. Independent variable are knowledge of local legislators about the budget. Dependent variable is local financial control. Moderating variable are public participation and public policy transparancy.Respondents in this study are legislative assembly at regency and city of Bima, Nusa Tenggara Barat Province. The data was collected by the survey. Data analysis techniques using simple linear regression and using moderated regression analysis. The result of this study indicated that first, knowledge of the legislators about the budget have effect to the local financial control.Â  Second,Â  public participation able to moderate the effect of participation in knowledge of legislators about the budget to the local financial control. Third, the transparency of public policy able to moderate the effect of knowledge of legislators about the budget to the local financial control.